Primary hepatic neuroendocrine tumor. (17th June 2021) - Tuan Linh, Le; Minh Duc, Nguyen; Tu Minh, Hoang; Ngoc Cuong, Nguyen; Thu Ha, Vuong; Luan, Dao-Thi; Tra My, Thieu-Thi; Van Lenh, Bui
Abstract : Summary: Primary hepatic neuroendocrine tumor (PHNET) is a rare type of neuroendocrine tumor (NET) that is also a primary hepatic tumor. Patients are present with almost no specific clinical symptoms and typically present with negative test results and atypical imaging characteristics; therefore, the differentiation of PHNET from other types of primary hepatic masses can be very difficult. In this article, we describe a case of PHNET that mimicked a liver helminth infection in a 57-year-old man. The diagnosis of PHNET in this patient was challenging, and the final diagnosis was based on imaging, histopathology features, and long-term follow-up. Learning points: An uncommon type of neuroendocrine tumor (NET) is a primary hepatic neuroendocrine tumor (PHNET). Primary hepatic neuroendocrine tumors are rare NET lesions found in the liver, characterized by non-specific clinical and imaging results, which can be easily confused with other liver lesions, including HCC and parasitic lesions. To have a conclusive diagnosis and classification, a mixture of many medical assessment techniques, such as imaging, gastrointestinal endoscopy, nuclear medicine, anatomy, including histopathology, and immunohistochemistry, is essential.